Front Cover. Issue 3 (5th August 2020) - Unknown
Abstract : A dual‐frequency intravascular photoacoustic/ultrasound catheter is developed and validated for lipid‐rich atherosclerotic plaque detection. By combining low‐frequency transducer for highly sensitive lipid detection and high‐frequency transducer for accurate localization in a single catheter with 1 mm diameter, this dual‐frequency catheter design largely improves the performance of intravascular photoacoustic imaging. It takes a step forward for the translation of this imaging modality for identification of vulnerable plaque in the vascular wall and perivascular lipid. Further details can be found in the article by Yingchun Cao, Mouhamad Alloosh, Michael Sturek, and Ji‐Xin Cheng (e202000004 ). Abstract : A dual‐frequency intravascular photoacoustic/ultrasound catheter is developed and validated for lipid‐rich atherosclerotic plaque detection. By combining low‐frequency transducer for highly sensitive lipid detection and high‐frequency transducer for accurate localization in a single catheter with 1 mm diameter, this dual‐frequency catheter design largely improves the performance of intravascular photoacoustic imaging. It takes a step forward for the translation of this imaging modality for identification of vulnerable plaque in the vascular wall and perivascular lipid. Further details can be found in the article by Yingchun Cao, Mouhamad Alloosh, Michael Sturek, and Ji‐Xin Cheng (e202000004 ).